Associação entre alterações motoras e mucosite oral em crianças e adolescentes com câncer - Lucena, Nyellisonn Nando Nóbrega de (2017)
The antineoplastic treatment can cause adverse effects that affect the physical and psychosocial well-being, besides limiting the day to day of the child, thus compromising the motor activities. Other changes observed three times more in children than in adults are complications of the oral cavity, such as oral mucositis. The objective of the study was to associate the motor alterations and oral mucositis of children and adolescents with cancer, who underwent antineoplastic treatment at the Hospital Napoleão Laureano, in the city of João Pessoa - PB. It is an observational, cross-sectional and analytical study, carried out from April to September 2017, with a sample of 70 children and adolescents aged 2 to 19 years. A semi-structured questionnaire was used, as well as the Oral Assessment Guide (OAG), and domains of the International Classification of Functioning Disability and Health (CIF), with clinical data collected by a calibrated examiner (Kappa> 0.75). Logistic regression was performed by the backward method, adopting a significance level of 5%. Oncopediatrous patients presented a predominance of males (54.3%, n = 38), with a mean of 10.9 years, prevalence of self-reported brown color (52.9%; n = 37); (68.6%, n = 48), and with monthly family income of up to 2 minimum wages (87.1%, n = 61). The majority of children and adolescents presented haematological type neoplasia (51.4%, n = 36), and (30.0%; 21) had a diagnosis of acute lymphoid leukemia. As for solid tumors (48.6%; n = 34), the highest prevalence was Osteosarcoma (14.3%; n = 10). Regarding the most widely used antineoplastic treatment, chemotherapy was the most cited (42.9%; n = 30). The presence of oral mucositis (31.4%; n = 22), and the predominance of mild impairment in walking ability (30.0%; n = 21) and dislocation (28.6%; = 20), as well as a mild and severe impairment in the health care capacity (25.7%; n = 18). The chance of developing oral mucositis was associated with primary education (OR = 4.6, [2.9171, 6.2255]), hematological tumor (OR = 5.4, [-1.2202, 1.5868]), severe difficulty in maintaining (OR = 9.9, [8.1778, 11.8044]) and severe difficulty in walking ability (OR = 26.8, [23.1818, 29.6235]). The study reveals that motor changes may influence the development of oral mucositis.